EU autonomy, the Brussels Effect, and the rise of global economic protectionism - Matthias Bauer; Dyuti Pandya (European Centre for International Political Economy (ECIPE), 2024)
The Brussels Effect, once emblematic of the EU's alleged influence in shaping global regulations, has now become a factor contributing to global regulatory fragmentation. The EU must recalibrate its trajectory towards a liberal and rules-based trading order, prioritizing widespread regulatory liberalization to counteract the risks of global protectionism and regulatory spirals. A holistic approach, both internally and globally, is crucial to prevent regulatory and subsidy spirals on a global scale. This recalibration is essential to keep global markets open and enhance the EU's own economic and technological competitiveness.
Keywords: 330; Globalization; International economy; Protectionism; Foreign trade; Trade barriers; EU countries; World; Globalisierung; Internationale Wirtschaft; Protektionismus; Außenhandel; Handelshemmnisse; EU-Staaten; Welt